Suspicion Vaccines, Hesitancy, and the Affective Politics of Protection in Barbados - Charles, Nicole (Duke University Press, 2022)
In 2014 Barbados introduced a vaccine to prevent certain strains of the human papillomavirus (HPV) and reduce the risk of cervical cancer in young women. Despite the disproportionate burden of cervical cancer in the Caribbean, many Afro-Barbadians chose not to immunize their daughters. In Suspicion, Nicole Charles reframes Afro-Barbadian vaccine refusal from a question of hesitancy to one of suspicion. Drawing on ethnographic fieldwork, black feminist theory, transnational feminist studies and science and technology studies, Charles foregrounds Afro-Barbadians' gut feelings and emotions and the lingering trauma of colonial and biopolitical violence. She shows that suspicion, far from being irrational, is a fraught and generative affective orientation grounded in concrete histories of mistrust of government and coercive medical practices foisted on colonized peoples. By contextualizing suspicion within these longer cultural and political histories, Charles troubles traditional narratives of vaccine hesitancy while offering new entry points into discussions on racialized biopolitics, neocolonialism, care, affect, and biomedicine across the Black diaspora.Duke University Press Scholars of Color First Book Award recipient